QUANTUM LEARNING SEBAGAI UPAYA GURU PENDIDIKAN ANAK USIA DINI MENJADI PENDIDIK YANG MENYENANGKAN - Umu Da'watul Choiro; Mira Shodiqoh (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2018)
Teaching and learning activities will make a difference for those who study and teach. This suggests that educators also play a role in learning success. Educators in the learning process must have a strategy to be able to deliver teaching materials to learners. Quantum is the interaction that convert energy into light, because all the energy is in the learning process of life and contains a diversity and inter determinisme. The concept of quantum learning in learning can be applied with the power of ambak or motivation, the arrangement of the learning environment, the fertilization of the attitude to become champion, the liberation of learning style, the habit of recording, the reading habit, the creativity of the students and the training of memory strength.